1995
DOI: 10.1007/bf00368891
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Influenza A virus infection in patients with acute or chronic leukemia

Abstract: Influenza infection is a significant cause of morbidity and mortality in immunocompromised hosts, but its importance in adult cancer patients is largely undescribed. We therefore conducted a prospective study of the incidence and clinical features of influenza infection in patients with acute or chronic leukemia. The cohort, which consisted of all adult leukemia patients undergoing remission-induction chemotherapy during the 1991-1992 influenza epidemic, was followed prospectively for development of signs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 20 publications
3
32
0
Order By: Relevance
“…Whether or not influenza vaccination should be systematically offered to cancer patients remains controversial, mainly because the quality of immune responses elicited by seasonal influenza vaccines is difficult to interpret as a result of previous immunizations, previous infections, and patient heterogeneity [2,8,[23][24][25][26]. Because the majority of adults are unlikely to have been exposed to or immunized against the new H1N1 strain of influenza, we postulated that the influenza A/H1N1 pandemic observed in 2009 provided a unique opportunity to unravel this controversy.…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not influenza vaccination should be systematically offered to cancer patients remains controversial, mainly because the quality of immune responses elicited by seasonal influenza vaccines is difficult to interpret as a result of previous immunizations, previous infections, and patient heterogeneity [2,8,[23][24][25][26]. Because the majority of adults are unlikely to have been exposed to or immunized against the new H1N1 strain of influenza, we postulated that the influenza A/H1N1 pandemic observed in 2009 provided a unique opportunity to unravel this controversy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of seasonal influenza in HCT recipients have consistently demonstrated a higher rate of progression to LRD and need for mechanical ventilatory support, 6 prolonged viral shedding, 23 and a higher mortality 3,[24][25][26] in HCT recipients than in the general population. Although rates of infection and hospitalization after 2009 influenza H1N1 are remarkably different by age group from rates reported in previous years, 27 clinical disease in the general population after infection with 2009 H1N1 and seasonal influenza have been shown to be remarkably similar with regard to overall disease severity and rates of complications.…”
Section: Discussionmentioning
confidence: 99%
“…A few small series have documented seasonal influenza outbreaks among such patients, demonstrating the susceptibility of immunocompromised populations. [11][12][13][14] These limited reports suggest that cancer patients are at a high risk for acquisition of influenza in both the community and health care settings.…”
Section: Epidemiologymentioning
confidence: 99%